2006
DOI: 10.1016/j.jlumin.2005.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental photophysical studies of the tris(4,4,4-trifluoro-1-(1-naphthyl)-1,3-butanedionate) (2,2′-bipiridyl)-europium(III)

Abstract: The complexes tris(4,4,4-Trifluoro-1-(1-naphthyl)-1,3-butanedionate) (2,2 0 -bipiridyl) Ln(III), Ln(tan) 3 bipy, where Ln(III) ¼ Eu 3+ and Gd 3+ have been synthesized, characterized and their photophysical properties (absorption, excitation and luminescence spectra and emission quantum yield) investigated down to 4.2 K. The Eu(tan) 3 bipy complex has its molecular structure experimentally determined using X-ray crystallography and theoretically using the SMLC/AM1 method as well as their electronic singlet and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…The excitation spectra of the systems under investigation clearly confirm a more efficient emission of crystal (2). Because the two structural isomeric forms of Eu(TAN) 3 dipy have been investigated and reported [6,7], we also assumed two isomers in the sample with phenanthroline. This assumption was also supported by the fact that the crystals under study were very sensitive on energy of excitation.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The excitation spectra of the systems under investigation clearly confirm a more efficient emission of crystal (2). Because the two structural isomeric forms of Eu(TAN) 3 dipy have been investigated and reported [6,7], we also assumed two isomers in the sample with phenanthroline. This assumption was also supported by the fact that the crystals under study were very sensitive on energy of excitation.…”
Section: Resultsmentioning
confidence: 68%
“…However, only the block form exists without contamination of the second phase. The optical behaviour of Eu(TAN) 3 dipy single crystals in form of blocks was investigated in detail by Donega and co-workers [7]. In order to compare the photoemission behaviour of the two …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigations reporting the use and/or development of theoretical models or methodologies have been discussed in the literature [8,12,13,15,17,28,43,55,56,86,[199][200][201][202][203][204][205][206][207].…”
Section: Theoretical Methods and Methodologiesmentioning
confidence: 99%
“…In the last decade, the new materials based on lanthanide complexes have been studied with particular interest for applications as highly efficient light conversion molecular devices. They can be used in wide range of processes and new technologies, such as fluorescent lighting, electroluminescence color displays, luminescent labels in bioaffinity assays, bioinorganic sensors, and high technology optics and optoelectronic applications [2][3][4][5][6][7][8]. Weissman in 1942 reported that lanthanide can be improved by using an intramolecular energy transfer, the antenna effect [1].…”
Section: Introductionmentioning
confidence: 99%